PELATIHAN SOFTWARE SIMULASI ELEKTRONIKA TINKERCAD UNTUK GURU FISIKA SMA KOTA SAMARINDA DAN SEKITARNYA - Nurhanafi, Kholis; Zarkasi, Ahmad; Putri, Erlinda Ratnasari; Putri, Devina Rayzi Perwitasari Sutaji; Syahrir, Syahrir; Ummah, Auliya Rahmatul (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
School learning demands an optimal learning experience to fulfill the learning outcomes. At the Senior High School level, several science topics, particularly physics, require simulations to enhance students' understanding. A community service initiative was carried out in the form of training on using TinkerCad electronics simulation software for high school physics teachers in Samarinda and its surrounding areas. This activity aimed to provide physics teachers with alternative teaching media, particularly for the topic of electronics at the high school level. The training was attended by 21 participants and conducted using lectures, demonstrations, and mentoring methods. Based on the interview results, the majority of participants were unfamiliar with the TinkerCad software, making this training a valuable new resource for high school physics teachers in Samarinda and the surrounding regions.